2021
DOI: 10.1111/josi.12486
|View full text |Cite
|
Sign up to set email alerts
|

Raising justice‐minded youth: Parental ethnic‐racial and political socialization and Black youth's critical consciousness

Abstract: Her research examines how youth develop beliefs, feelings, and actions that challenge racism (i.e., youth critical racial consciousness development). In collaboration with youth, schools, parents, and community organizations, she co-creates opportunities that facilitate youths' critical racial consciousness development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 51 publications
2
47
2
1
Order By: Relevance
“…Our findings are in contrast to Bañales et al. (2021), who did not find a significant relation between critical consciousness socialization and critical reflection using the same measures. However, they did find that critical consciousness socialization was directly related to interpersonal and communal action, wherein in our study, we saw an indirect relation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are in contrast to Bañales et al. (2021), who did not find a significant relation between critical consciousness socialization and critical reflection using the same measures. However, they did find that critical consciousness socialization was directly related to interpersonal and communal action, wherein in our study, we saw an indirect relation.…”
Section: Discussioncontrasting
confidence: 99%
“…We further saw that perceptions of teachers addressing racism and inequality in the curriculum (critical consciousness socialization) were also related to critical reflection (Anyiwo et al, 2018;Cammarota & Romero, 2011;Richards-Schuster & Aldana, 2013;Seider et al, 2017). Our findings are in contrast to Bañales et al (2021), who did not find a significant relation between critical consciousness socialization and critical reflection using the same measures. However, they did find that critical consciousness socialization was directly related to interpersonal and communal action, wherein in our study, we saw an indirect relation.…”
Section: Discussioncontrasting
confidence: 67%
“…This section begins with Bañales et al. (2021) investigation of the relationship between parents’ political socialization and ERS in Black families and the extent to which these messages are related to youth's critical consciousness. This represents an important but understudied issue, because discussion of race in Black families inherently stem from parents’ desire to promote Black youths’ resistance to dominant cultural narratives and to protect them from oppressive structures and interactions.…”
Section: Organization Of This Issuementioning
confidence: 99%
“…This discrepancy has been hypothesized to be related to stress and depression. Thus, ERS strategies could focus on providing support and messages about the realities associated with societal constraints on mobility (Bañales et al., in, press).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…A long tradition of research on ethnic‐racial socialization (ERS) has examined how parents transmit information regarding race and ethnicity to their children (Hughes et al., 2006) and how this shapes their identity formation (Rivas‐Drake & Umaña‐Taylor, 2019). This research has demonstrated how parents of ethnic minority groups prepare their children for potential discrimination and barriers related to stigma, bias, and access to resources (Bañales et al., in press; Hughes et al., 2006). Two considerations warrant an additional examination of adolescents’ awareness of social mobility and social hierarchies.…”
Section: Introductionmentioning
confidence: 99%